Exploring print media coverage of elite athletes’ mental illness between 2010 and 2023 in Germany: a quantitative content analysis - Hapig, Marcia; Zurstiege, Guido; Mayer, Jochen; Thiel, Ansgar; John, Jannika M. (Frontiers in Sports and Active Living, 2024)
Objectives: Recently, the stereotype of elite athletes' invulnerabilty has begun to be challenged by an increasing number of elite athletes who talk openly about struggling with mental health. Relatedly, previous research has focused primarily on specific incidents like the media's portrayal of personal disclosures. The purpose of this study was to expand this perspective and give a systematic overview of media coverage related to elite athletes' mental illness by examining more than one decade (2010-2023) of German print media reporting. Specifically, we were interested in changes over time and between broadsheet and tabloid press regarding content-related and formal aspects. Method: Based on a systematic search and screening process in eleven German newspapers and magazines, 699 print media articles were analyzed with a codebook, forming a framework of contentrelated (reported mental disorder; central thematic focus; sources of comments and quotations; perspectives on the high-performance sports system) and formal categories (article genre; elements of responsible journalism). Univariate analyses and binary logistic regression models were used to examine changes over time (2010-2016 vs. 2017-2023) and differences between types of press (tabloid vs. broadsheet press) regarding content-related and formal characteristics. Results: The results indicate an enhanced awareness towards the topic of mental illness and those affected in recent years within German print media. This was demonstrated by the increased integration of responsible reporting elements, the inclusion of diversified perspectives and the considerate selection of content. Despite this positive trend over time, the findings also suggest that media reporting in the tabloid press bears an increased risk for inappropriate storytelling, focusing primarily on personal tragedies. Conclusion: As personal fate of prominent figures like elite athletes will always meet great interest in the public, it is of utmost importance that the media report responsibly and promote critical thinking in society. The study shows the media's willingness to question conventional ideals embedded in the sports culture and take a more critical approach to the topic of mental illness in high-performance sports. By demonstrating a greater understanding of the importance and the seriousness of the issue, the media might also contribute to improved mental health awareness in society.